CCTA-derived functional and morphological features and their comparative performance in predicting impaired coronary vasodilatation by PET-myocardial perfusion imaging. (8th February 2021) - Kalykakis, G; Antonopoulos, A; Pitsariotis, T; Siogkas, P; Exarchos, T; Kafouris, P; Liga, R; Giannopoulos, A; Scolte, A; Kaufmann, P; Parodi, O; Knuuti, J; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): This work was supported in part from European Regional Development Fund, Operational Programme "Competitiveness, Entrepreneurship and Innovation 2014-2020 (EPAnEK)", titled: The Greek Research Infrastructure for Personalized Medicine (pMED-GR), no. GR 5002802, and by Greece and the European Union (European Social Fund-ESF) through the Operational Programme «Human Resources Development, Education and Lifelong Learning 2014-2020» in the context of the project "Assessment of coronary atherosclerosis: a new complete, anatomo-functional, morphological and biomechanical approach", Project no. 504776 onbehalf: EVINCI-SMARTOOL Background/Objectives: The relationship between biomechanical characteristics of a coronary lesion with myocardial blood flow has not been studied. We investigated the relationship between local endothelial shear stress (ESS) and computed tomography coronary angiography (CTCA)-derived anatomical and plaque characteristics data with impaired vasodilating capability assessed by positron emission tomography myocardial perfusion imaging (PET-MPI). Methods: A total of 92 coronary vessels of 53 patients who have undergone both CTCA and PET-MPI with 15O-water or 13N-ammonia were analysed. PET was considered abnormal when > 1 contiguous segments showed both stress Myocardial Blood Flow (MBF) ≤2.3mL/g/min and Myocardial Flow Reserve (MFR) ≤2.5 for 15O-water or <1.79 mL/g/min and ≤2.0 for 13N-ammonia respectively.  CTCA images were used to assess stenosis severity, lesion specific total plaque volume (PV), non-calcified PV and calcified PV as well as plaque phenotype. ESS was calculated for the full length of a lesion (total), as well as in the proximal, minimum lumen area and distal lesion segments. Results: ESS was weakly correlated with total PV (rho = 0.273, p = 0.008), non-calcified PV (rho = 0.247, p = 0.017) and the volume of necrotic core (rho = 0.242, p = 0.02). ESS increased progressively with stenosis severity (p ≤ 0.001). ΕSS was also higher in functionally significant vs. non-significant lesions (10.4 [8.04-54.4] Pa vs. 3.9 [2.32-7.29] Pa, p ≤0.001). Addition of ESS to stenosis severity improved prediction (Δ[AUC]:0.113, 95% CI: 0.055 to 0.171, p = 0.0001) of functionally significant lesions. Conclusion: There is a weak positive association between lesion-specific ESS and plaque volume. ESS increases progressively with stenosis severity and is higher in functionally significant lesions by PET-MPI. The addition of ESS to CTCA-anatomical information improves prediction of an abnormal PET-MPI result.